Peran Human Capital Manajemen Terhadap Kinerja Karyawan (Literatur Review MSDM) - Maulana Rohman; Jumawan Jumawan; Hadita Hadita (Student Research Journal, 2023)
: A literature article reviewing the role of human capital on employee performance is an article that aims to form a research hypothesis regarding the role of variables that will be used in further research, within the Human Resource Management environment. The writing method used is descriptive qualitative with a literature review approach where the data comes from various online sources, such as Google Scholar and the use of the Mendeley application. The results found in this article are that there is a role given by the human capital variable to employee performance variables. Apart from human capital as an influencing variable, there are many other factors and roles such as work motivation, compensation and leadership style.